Nuclear Ribosomal DNA ITS-2 Sequence Characterization of Fasciola hepatica and Galba truncatula - K Ashrafi; J Massoud; K Holakouie Naieni; MA Jo-Afshani; M Mahmoodi; N Ebadati; SM Rezvani; P Artigas; MD Bargues; S Mas-Coma (Tehran University of Medical Sciences, 2007)
Background:  Human fascioliasis is an important health problem in the province of Gilan, at the Caspian Sea, Iran. There is the overlapping of both fasciolid species, Fasciola hepatica and F. gigantica. Recent studies on both domestic animal and lymnaeid infection furnished evidence suggesting that F. gigantica and Radix gedrosiana may be the main fasciolid and lymnaeid involved in the disease in that province, controversy still being there concerning the presence and importance of F. hepatica and other lymnaeid species. The present paper includes the results of studies on Galba truncatula and the first finding of natural infection by F. hepatica in Gilan proved by molecular studies. Methods: Snail collections were carried out in summer, when their populations present the highest densities. Surveys on lymnaeids furnished the finding of a lymnaeid snail infected by trematode rediae and cercariae in the mountains of Talesh, in the Asalem district, western Gilan. Results: Nuclear ribosomal DNA ITS-2 sequences proved that they were F. hepatica and G. truncatula. The liver fluke ITS-2 sequence was identical to that of F. hepatica from Spain and the Northern Bolivian Altiplano and that of G. truncatula to the haplotype H-2 known in Portugal, Spain, France and The Netherlands. Conclusion: This genetic characterization suggests that both may be also involved in human fascioliasis infection in Gilan.